2016
DOI: 10.21873/anticanres.11117
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Associated with Weight Loss After Esophagectomy for Esophageal Cancer

Abstract: Abstract. Background/Aim: This study aimed to clarify the relationship between dosimetric factors and parotid gland (PG) atrophy after carbon ion radiotherapy (C-ion RT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…reported that the absence of pyloroplasty was the sole risk factor for > 10% weight loss of PWL one year after esophagectomy . A retrospective study with six months follow‐up after esophagectomy showed that preoperative BMI and a shorter LOS resulted in > 10% weight loss . In this study, however, except for VCP, we found no definitive association between the PBW, BMI, and LOS with long‐term SWL.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…reported that the absence of pyloroplasty was the sole risk factor for > 10% weight loss of PWL one year after esophagectomy . A retrospective study with six months follow‐up after esophagectomy showed that preoperative BMI and a shorter LOS resulted in > 10% weight loss . In this study, however, except for VCP, we found no definitive association between the PBW, BMI, and LOS with long‐term SWL.…”
Section: Discussioncontrasting
confidence: 84%
“…5 A retrospective study with six months follow-up after esophagectomy showed that preoperative BMI and a shorter LOS resulted in > 10% weight loss. 44 In this study, however, except for VCP, we found no definitive association between the PBW, BMI, and LOS with long-term SWL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reconstruction of the gastric tube, which is commonly required with esophagectomy, is associated with a high incidence of anastomotic leakage [1]. From a clinical perspective, postoperative weight loss is common after esophagectomy, even in the absence of any complications [4], with severe weight loss being associated with a poor prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, unintentional weight loss is a major concern both before and during the treatment of cancer. Several studies have demonstrated that weight loss before esophageal cancer resection might be related to the postoperative survival [6][7][8][9][10][11][12]. To our knowledge, no research has focused on weight loss during neoadjuvant CRT or on the relationship between this weight loss and the survival outcomes in patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall survival (OS) varies in such patients, and some fail to benefit from neoadjuvant chemoradiotherapy, indicating a need to identify the factors associated with the prognosis and provide more information about the most appropriate clinical interventions to improve outcomes among highrisk patients. One such factor is weight loss, which is common and often occurs by the time of diagnosis or during treatment in patients with esophageal cancer [4][5][6][7][8]. Although weight loss before treatment has been shown to be a key prognostic indicator of the OS in such patients [9-demographics, neoadjuvant treatment, toxicity, weight records and follow-up results were reviewed in detail from the medical records and the follow-up system.…”
Section: Introductionmentioning
confidence: 99%